The Effect of Video Project-Based Learning on Students’ Speaking Skill - Iin, Wahyudi (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2022)
This research is entitled “Effectiveness of Video Project-Based Learning on students' English skills. This research employed a pre-experimental method. The data in this study were collected through a speaking test; pre-test and post-test. This study aims to measure the effectiveness of the use of video project-based learning methods on students' English skills. Thus, there are 35 samples involved in this study they were students from the English language study program, faculty of teacher training and education at the University of Lakidende Unaaha for the 2020/2021 academic year. The results of this study, in this case the paired sample T test, showed that the students' pre- test and post-test results were at level .00 or P less than .05, which means that project-based learning can significantly improve students' speaking skills. In addition, the application of this video project learning method is proven to increase students' self-confidence in speaking using English. This study provides suggestions for future researchers to focus on mastering or improving other skills.